Comparative study of LEO and GEO SSPS for some identified sites in India - Chaudhary K.; Vishvakarma B.R. (My University, 2025)
The analysis of satellite solar power station (SSPS) is carried out for some specified locations in India and consequently the performance of the system is evaluated for geostationary earth orbit (GEO)-based SSPS and low earth orbit (LEO)-based SSPS for sites located at different latitudes. The analysis of power, the received energy over a year, and the received energy during a day for the same beam intensity show better results for LEO-based SSPS system as compared to GEO-based system. However GEO-based system is advantageous in the sense that it will deliver constant energy to the load throughout a year. Thus it is concluded that GEO-based system is suitable for base load power plant. The weight of the rectenna and hence the space required for ground station for same power output for GEO-based system is greater than that for LEO-based system which will in turn increase the overall cost of the GEO-based system. These findings may help for judicious selection of orbit for placing the satellite for SSPS. © 2009 The Berkeley Electronic Press. All rights reserved.